Architecting the Overture: A Pedagogical Framework for Crafting High-Quality Research Introductions in Graduate EFL Contexts - Nur, Sahril; Sunra, La; Sakkir, Geminastiti (ELT Worldwide: Journal of English Language Teaching, 2025)
The introduction chapter is a critical hurdle for graduate students in English as a Foreign Language (EFL) contexts. It functions as a persuasive overture that must establish significance, delineate a clear scholarly gap, and articulate the study's purpose. This article provides a pedagogical framework for students and supervisors on constructing a high-quality research introduction. Drawing on genre analysis, specifically Swales’s Create a Research Space (CARS) model, the guide deconstructs the essential rhetorical moves for a compelling argument. Through a comparative analysis of strong and weak examples, it illustrates common pitfalls and effective strategies. The core of the article discusses the unique challenges faced by EFL scholars in contexts like Indonesia, proposing a scaffolded pedagogical model to improve research writing instruction. The aim is to equip emerging scholars with the conceptual tools and practical strategies to architect an introduction that meets the rigorous standards of international academic discourse.